Computation of thermodynamic parameters of binary metal systems with limited solubility of components in the solid α-phase - Shcherban, A.P.; Datsenko, O.A. (Вопросы атомной науки и техники, 2020)
In the region of the primary solid α-phase for systems with limited solubility thermodynamic quantities such as the partial enthalpy of dissolution Δ HαB, the activity coefficients γαB and the activities ααB in binary metal systems were calculated. The above-mentioned indicated values were determined from the relations that connect these parameters with the equilibrium distribution coefficient k0B and known thermodynamic quantities, such as the enthalpy variation ΔHплВ and entropy variation ΔSплВ during melting of component B. The calculation of equilibrium distribution coefficients using data from experimentally constructed solidus and liquidus lines of state diagrams was performed. The values and temperature dependences of the dissolution enthalpy for such systems as Ag–Mg, Nb–Ge, Mg–Al, Mg–Ag, Al–Mg, Ni–Ga, as well as the values and dependences of the activity coefficients γαB and activities ααB of the second component on these systems were determined. В області первинної твердої α-фази для систем з обмеженою розчинністю зроблено розрахунок значень таких термодинамічних величин, як парціальна ентальпія розчинення Δ H αB, коефіцієнти активності γαB і активність ααB компонентів у бінарних металевих системах. Вище зазначені величини визначали із співвідношень, які пов'язують ці параметри з рівноважним коефіцієнтом розподілу k0B і відомими термодинамічними величинами, такими як зміна ентальпії ΔHплВ і зміна ентропії ΔSплВ при плавленні компонента В. Розрахунок рівноважних коефіцієнтів розподілу виконували з використанням даних експериментально побудованих ліній солідусу і ліквідусу діаграм стану. Визначено значення і температурні залежності ентальпії розчинення для таких систем, як Ag–Mg, Nb–Ge, Mg–Al, Mg–Ag, Al–Mg, Ni–Ga, а також значення і залежності від температури розчинення коефіцієнтів активності γαB та активність ααB другого компонента в цих системах. В области первичной твердой α-фазы для систем с ограниченной растворимостью выполнен расчет значений таких термодинамических величин, как парциальная энтальпия растворения Δ HαB, коэффициенты активности γαB и активность ααB компонентов в двойных металлических системах. Выше указанные величины определяли из соотношений, которые связывают эти параметры с равновесным коэффициентом распределения k0B и известными термодинамическими величинами, такими как изменения энтальпии ΔHплВ и энтропии ΔSплВ при плавлении компонента В. Расчет равновесных коэффициентов распределения выполняли с использованием данных экспериментально построенных линий солидуса и ликвидуса диаграмм состояния. Определены значения и зависимости от температуры энтальпии растворения для таких систем, как Ag–Mg, Nb–Ge, Mg–Al, Mg–Ag, Al–Mg, Ni–Ga, а также значения и зависимости от температуры растворения коэффициентов активности γαB и активность ααB второго компонента в этих системах.